Bulk-nano spark plasma sintered Fe-Si-B-Cu-Nb based magnetic alloys. (September 2020) - Larimian, T.; Chaudhary, V.; Christudasjustus, J.; Ramanujan, R.V.; Gupta, R.; Borkar, T.
Abstract: Iron-based soft magnetic alloys (FeSiB, FeSiBNb, FeSiBCu, and FeSiBNbCu (Finemet)) have been fabricated via mechanical alloying followed by spark plasma sintering (SPS) process. FeSiB alloy powder was obtained by high energy ball milling of an elemental blend Fe, Si, and B powders. The effect of milling time on crystallite size and phase transformation was studied. Additionally, FeSiBCu, FeSiBNb, and FeSiBCuNb alloy powders were milled to study the effect of Cu and Nb on phase transformation, mechanical, and magnetic behavior. The mechanically alloyed powders were sintered via SPS process to achieve full densification. The microhardness and magnetic permeability of sintered FeSiB alloys were found to be increased monotonically with milling time primarily due to the smaller crystallite size and more uniform microstructure. Interestingly, the alloying of Cu or (and) Nb to FeSiB resulted in higher saturation magnetization and lower coercivity mainly due to large volume fraction of α-Fe3 Si nanocrystals. Overall, these alloys exhibit reasonably good soft magnetic behavior along with excellent microhardness. Mechanical alloying followed by spark plasma sintering opens up a new avenue of processing amorphous-nanocrystalline alloys into bulk shape with good mechanical and magnetic properties. Highlights: Iron-based soft magnetic alloys processed by mechanical alloying followed by SPS. Microhardness of alloys increases with increasing milling time. Crystallite size of iron-based alloys decreases with increasing milling time. All alloys exhibited good saturation magnetization and lower coercivity.